Evaluation of a new rapid immunochromatographic assay for the detection of GES-producing Gram-negative bacteria. (28th March 2023) - Gonzalez, Camille; Volland, Hervé; Oueslati, Saoussen; Niol, Léa; Legrand, Camille; Francius, Laura; Chalin, Arnaud; Vogel, Anaïs; Simon, Stéphanie; Naas, Thierry
Abstract: Background: As carbapenemase-producing Enterobacterales are increasingly reported worldwide, their rapid detection is crucial to reduce their spread and prevent infections and outbreaks. Lateral flow immunoassays (LFIAs) have become major tools for the detection of carbapenemases. However, as for most commercially available assays, only the five main carbapenemases are targeted. Objectives: Here, we have developed and evaluated an LFIA prototype for the rapid and reliable detection of the increasingly identified GES-type β-lactamases. Methods: The GES LFIA was validated on 103 well-characterized Gram-negative isolates expressing various β-lactamases grown on Mueller–Hinton (MH) agar, chromogenic, and chromogenic/selective media. Results: The limit of detection of the assay was 10 6 cfu per test with bacteria grown on MH agar plates. GES LFIA accurately detected GES-type β-lactamases irrespective of the culture media and the bacterial host. The GES LFIA was not able to distinguish between GES-ESBLs and GES-carbapenemases. Because GES enzymes are still rare, their detection as an ESBL or a carbapenemase remains important, especially because extensive use of carbapenems to treat ESBL infections may select for GES variants capable of hydrolysing carbapenems. Conclusions: The GES LFIA is efficient, rapid and easy to implement in the routine workflow of a clinical microbiology laboratory for the confirmation of GES-type β-lactamases. Combining it with immunochromatographic assays targeting the five main carbapenemases (KPC, NDM, VIM, IMP and OXA-48) would improve the overall sensitivity for the most frequently encountered carbapenemases and ESBLs, especially in non-fermenters.